Molecular techniques applied to the study of bacteriosis in rice (Oryza sativa L.): bibliometric analysis of scientific production (Agroindustria, Sociedad y Ambiente, 2025)
The main objective of this study was to analyze the molecular techniques used for the identification and characterization of phytopathogenic bacteria associated with rice (Oryza sativa L.) bacteriosis, through a bibliometric analysis of scientific production published between 2013 and 2023. The methodology involved a systematic literature review in databases such as Redalyc, Dialnet, Scielo, and Google Scholar, using keywords related to bacteriosis and molecular techniques in rice. Scientific articles and theses were collected, with information classified by author, year, journal, country, studied pathogen, molecular technique, and study type. Data processing was performed in Excel, generating matrices and charts to analyze indicators such as technique used, study topic, causal agent, geographic distribution, author productivity, and publication years. Results show that PCR and 16S rDNA gene sequencing are the most commonly used techniques, with bacterial identification studies predominating. Xanthomonas oryzae is the most studied pathogen, and China leads scientific production. It is concluded that molecular techniques have improved the speed and accuracy of phytopathogenic bacteria identification in rice, although technological access remains limited in some countries. It is recommended to promote training and technology transfer, as well as strengthen international research networks to optimize the management of rice bacteriosis.
Keywords: rice, bacteriosis, molecular techniques, bibliometric analysis, Xanthomonas oryzae